2017
DOI: 10.1108/itse-02-2016-0006
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing undergraduate students’ acceptance of a haptic interface for learning gross anatomy

Abstract: Biographical Details:Soonja Yeom, is a Lecturer in School of Engineering and ICT. She teaches computer security and programming for the internet. Currently she is a PhD candidate with a thesis titled 'Undergraduate student acceptance of haptic simulation in gross anatomy learning'. Her research interests include technology-enhanced learning, human computer interface, and computer security.Derek Choi-Lundberg, PhD, is Senior Lecturer in Anatomy, School of Medicine, University of Tasmania. He teaches gross anato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 70 publications
(83 reference statements)
0
8
0
1
Order By: Relevance
“…Then, attention was focused on medical students' levels of acceptance of and the usability of the system. It was reported that the students found the system practical, easy, and useful (Yeom et al, ). Patirupanusara () developed a MagicBook for anatomy course through marker‐based AR technology.…”
Section: Introductionmentioning
confidence: 99%
“…Then, attention was focused on medical students' levels of acceptance of and the usability of the system. It was reported that the students found the system practical, easy, and useful (Yeom et al, ). Patirupanusara () developed a MagicBook for anatomy course through marker‐based AR technology.…”
Section: Introductionmentioning
confidence: 99%
“…Çalışmalarda AG teknolojisiyle karmaşık anatomik yapıların öğretimine yönelik sistemler ve canlı kitap uygulamaları geliştirilmesine odaklanıldığı görülmektedir. Öğrencilerin anatomi öğretimine yönelik AG sistemlerini kullanışlı, kolay ve faydalı buldukları, bu sistemlerin iyi bir görselleştirme sağladığı belirtilmektedir (Meng et al, 2010;Thomas et al, 2010;Yeom et al, 2013). AG teknolojisinin MAG uygulamaları yönünde gelişmesi tıp eğitimi alanında kullanılabilecek MAG uygulamalarına yönelim yaşanmasını sağlamıştır.…”
Section: Introductionunclassified
“…Therefore, familiarity with some aspects of the system could explain this relationship (Yeom et al, 2017). On the contrary, several studies have shown that previous experience with ICTs did not affect the learning outcomes when they were assessed using traditional questions (Yammine and Violato, 2015).…”
Section: Accepted Articlementioning
confidence: 98%
“…Males and females were considered separately for the assignation of participants to the methods. This procedure was done to maintain a comparable number of males assigned to each of the learning methods, as gender differences may exist in the acceptance of technologies for learning (Yeom et al, 2017). However, the…”
Section: Limitations Of the Studymentioning
confidence: 99%